Overview of bioenergy use and production in sub-Saharan Africa - Akakpo, K.; Fontodji, J.K.; Lare, Y.; Adam, R.; Kokutse, A.D.; Kokou, K. (Renewable & sustainable energy reviews, 2024)
The importance of biomass energy and the challenges of the sector in Sub-Saharan Africa has for a long time been the subject of considerable research. Unfortunately, the results of this work remain scattered and fragmented. This study aims to assess the current state of knowledge on the use and production of bioenergy in sub-Saharan Africa in order to guide the actors involved in the modernization process. The study is based on a cross-analysis of scientific publications on bioenergy for this region. The publications obtained are divided into predefined thematics, year of publication and geographical origin of the research centers. Statistical processing, especially Principal Component Analysis was carried out to establish a link between the countries of the research centers and the addressed thematic. The results showed that 2009 is a pivotal year for research in the field of bioenergy in Sub-Saharan Africa. France has been identified as the country most involved in research into the development of bioenergy in the region. Despite modernization efforts, the production and use of biomass for energy purposes in Sub-Saharan Africa remains traditional. However, the study reveals that apart from wood which is becoming scarce, Sub-Saharan Africa has many biomass ressources with high energy potential which can significantly contribute to satisfying local energy needs. Unfortunately, their valorization into modern renewable energy remains embryonic. The challenges to be met are 40 % technological, 32 % land-related and 28 % socio-political. A replicable bioenergy modernization assessment tool baptized "3P concept" based on nine objective criteria is developed. [Display omitted] •A temporal evolution of bioenergy research in sub-Saharan Africa is traced.•A replicable tool for assessing bioenergy modernization level is set up.•Bioenergy modernization in Sub-Saharan Africa is assessed.•Challenges facing the sector are classified in order.•Countries supporting bioenergy modernization research in Sub-Saharan Africa are known.